Web-Gis Application Of Agricultural And Food Crop Management - Salahuddin Salahudin; Husaini Husaini; Anwar Anwar; Zulfan Zulfan (Journal of Engineering and Scientific Research, 2020)
This paper discusses web-based applications in the agricultural and food crops sectors in North Aceh district, Aceh Province, Indonesia. The agricultural and food crops sector is a mainstay sector of the people of North Aceh and local governments to move the economy and income of the local community. There are several superior agricultural products and food crops including rice, corn, sweet potatoes, green beans, long beans, cassava and potatoes. The North Aceh Government does not have sufficient applications to manage agricultural sector products. The research objective is to realize the independence of local food in order to support the national food security program. The mechanism used to design and make agricultural and food crop web applications starts from application design, application construction/coding, application testing and implementation system. After testing the web application by doing black box testing-white box and GUI testing to find out the side of the application display, application behavior and application durability. The results showed the application accuracy, stability and durability of the application reached 97.4%. The application web-based of agriculture and food crop management has been running as it should for mapping/GIS of superior agricultural commodities and GIS potential locations of agriculture and food crops in North Aceh.   Keywords: Applicaton, GUI, Black Box Testing, GIS